(untitled) (Global Journal of Human-Social Science, 2021)
The sustainability of a society is basically inclined to their access to the basic need of life food and in such occasion where there is unavailability of food and a corresponding unaccessibility of food by the members of society then the society is at the mercy of food insecurity and gruesomely death on a long run This paper examines the case of food insecurity ravaging Benue state of Nigeria in the face of the rising conflict amidst food producers farmers and herders what the cause of this conflict are how this conflict has affected food security and the solutions to end the conflict and boost food security within the state The paper discovered climate change and intolerance as the causes of the conflict loss of agro-proceed loss of agromanpower cessation of farmlands displacement of farmers and herders alike change of farming occupation fear of going to the farm rise in cost of food items and deprivation of access to markets as the effects of the conflict on food security in the region